Optimization of Chitinase Production from Lake Sediment Inhabitant Bacillus thuringiensis Strain LS1 and Bacillus cereus Strain LS2 - Sudha, Dr. S. (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: Chitinase production from freshwater lake sediment-derived bacteria by submerged fermentation and media optimization. Methodology: Isolation of bacteria from freshwater lake sediment by serial dilution followed by spread plate technique on colloidal chitin agar (CCA). The potential bacterial isolates were detected by qualitative cup plate assay and were identified by 16S rRNA sequencing. Optimization of the chitinase production was done by varying different physicochemical factors one at a time keeping the other factors constant. Results: Two isolates were selected for chitinase production based on the zone of clearance on CCA and were identified as Bacillus thuringiensis strain LS1 (MG948147) and Bacillus cereus strain LS2 (MG948148) based on 16S rRNA sequencing. The enhanced production of chitinase by B. thuringiensis strain LS1 was observed in minimal medium amended with 1% colloidal chitin, glucose as a carbon source, and malt extract as a nitrogen source, in pH 7.0, at 35Â°C in 72 h of incubation. The optimal condition for chitinase production by B. cereus strain LS2 was minimal medium amended with 1% colloidal chitin, sucrose as carbon source, and yeast extract as nitrogen source with pH 7.0 at 35Â°C in 96 h of incubation. Conclusion: Lake sediment bacterial community was screened for chitinase production and the potential strains were identified and its 16S rRNA sequences were submitted in GENE BANK.